EL LENGUAJE RADIOFÓNICO Y SU INCIDENCIA EN EL RATING DE RADIO VIVA DEL CANTÓN QUEVEDO - Flores Meza, Kimberly Stefania (2022)
Radio stations are quite relevant means of communication that have become a communication system that many people use to keep informed of the latest news of the day and what is happening in our city. However, the population listens to news programs, but rather chooses what they want to listen to, generating a rating, exemplifying the possibility of finding stations with good content, be it sports, entertainment, melody, and others. Radio is a medium that has been around for many years and has become popular to the point that it has already arrived on the internet and every day there are more radio stations that join the enormous network of information through this system. One of the benefits of the radio station is that we have the possibility of listening wherever we want to be, at the office or work, at home, on transport once we are driving at all times now technology provides us with this enormous tool to be able to hear, in this way we are doing a job and obtaining a rating since the vast majority of mobile devices already have the radio incorporated, we ourselves prepare our equipment to be able to choose the tune and listen to stations on the radio and thus earn a rise and fame persistently.